Sporotrichoid primary cutaneous nocardiosis: A rare case of isolated upper-limb involvement in a housewife - Juhi Fatima Sultan; Fatima Razvi; Nayeem Sadath Haneef; Sarwat Fatima (Wolters Kluwer Medknow Publications, 2024)
Nocardiosis is a rare infection due to a ubiquitous, gram-positive, weakly acid-fast, filamentous, aerobic bacteria, that are usually responsible for opportunistic infection in immunocompromised patients. Less frequently, nocardiosis can affect immunocompetent patients, causing primary cutaneous infections. Here we present a case of a 45-year-old housewife with a 12-day history of red painful nodules arranged linearly on her right upper limb, without any apparent history of injuries or comorbidities, albeit with a hobby of gardening. The unusual yet characteristic presentation, microbiological findings, and excellent response to co-trimoxazole therapy were consistent with a diagnosis of sporotrichoid primary cutaneous nocardiosis. The uncommon lymphocutaneous presentation is often misdiagnosed. Therefore, keeping a high index of suspicion in such cases is important to improve the cure rate and prevent complications.